Blockchain-Integrated Security Framework for Fog Networking of Connected Vehicles - Buhari, Abudhahir (Journal of ISMAC, 2024)
In the rapidly evolving domain of connected vehicles, ensuring robust security and efficient data management is paramount. Traditional centralized architectures struggle with latency, scalability, and vulnerability to single points of failure. This research proposes a novel Blockchain-Integrated Security Framework (BISF) for fog networking in connected vehicles. The BISF leverages blockchain technology to enhance data integrity, transparency, and security while utilizing fog computing to reduce latency and improve real-time data processing. The proposed framework integrates smart contracts for automated trust management and distributed ledgers for immutable data records. Simulation results demonstrate the effectiveness of BISF in enhancing security, reducing latency, and improving overall network performance compared to traditional centralized approaches.